PENERAPAN RAPID APPLICATION DEVELOPMENT PADA APLIKASI WAREHOUSE PT. INDONESIA TRC INDUSTRY - Selviana, Vina; Butsianto, Sufajar; S. Sunge, Aswan (Jurnal Teknoinfo, 2024)
In the midst of increasingly complex business dynamics, the need for efficiency in warehouse management is crucial for the smooth supply chain of a company, one of the solutions that is the main focus is the application of a web-based warehouse information system. PT. Indonesia TRC Industry is a manufacturing company. It was found that the management of item data is still done manually which has not been integrated with the database and only relies on the miscrosoft excel application. So there are difficulties in managing data goods where finding data in a certain period of time takes a long time. One solution to overcome existing problems PT. Indonesia TRC Industry needs to implement a website-based warehouse data management application that is integrated with the database. By using the Rapid Application Development (RAD) method. With the implementation of a website-based goods data management application, it can create an integrated application with a database, so that it can make it easier for users to find financial data at a certain period of time and make it easier to make stock reports.